A self-powered P–SSHI and boost hybrid interface circuit for Multi-PZTs and low voltage electromagnetic energy extraction. (May 2023) - Zeng, Wentao; Shi, Ge; Hu, Xiangzhan; Shi, Zhebin; Pan, Jiaheng; Sun, Qichao; Jia, Shengyao; Han, Jianqiang
Abstract: This paper presents a self-powered P–SSHI and boost hybrid interface circuit for multi-piezoelectric transducers (PZTs) and low-voltage electromagnetic energy extraction (MI-PSSHI-BOOST-HEC). The MI-PSSHI-BOOST-HEC uses a bridgeless voltage doubler rectifier to reduce the number of traditional rectifier bridge diodes and thus losses. Simulations and experiments show that the proposed circuit can extract energy from multiple PZTs with an arbitrary phase difference. The energy extracted from the EMG can be improved by a voltage doubler rectifier and boost structure. The described MI-PSSHI-BOOST-HEC circuit can extract 2.02 mW of the RMS power from a dual PZT input with an open-circuit amplitude of 12 V (30 Hz, 28 Hz) and an EMG (5 Hz) input with an open-circuit amplitude of 2 V. In addition, the oscillator in the boost structure is completely powered by the EMG, which means that the electric energy in the traditional energy storage capacitor is not consumed. This provides an alternative solution for extracting energy from EMGs and multi-PZTs.